2000
DOI: 10.1074/jbc.275.6.4507
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of Multispecific Organic Anion Transporter 4 Expressed in the Placenta

Abstract: A cDNA encoding a novel multispecific organic anion transporter, OAT4, was isolated from a human kidney cDNA library. The OAT4 cDNA consisted of 2210 base pairs that encoded a 550-amino acid residue protein with 12 putative membrane-spanning domains. The amino acid sequence of OAT4 showed 38 to 44% identity to those of other members of the OAT family. Northern blot analysis revealed that OAT4 mRNA is abundantly expressed in the placenta as well as in the kidney. When expressed in Xenopus oocytes, OAT4 mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
320
1
13

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 373 publications
(343 citation statements)
references
References 35 publications
9
320
1
13
Order By: Relevance
“…Trans-stimulation of OAT4 was not observed in earlier studies. Furthermore, unlike Oat1 and Oat3, OAT4's function was reported to be sodium-independent [72]. These findings contrasted with that of the renal basolateral tertiary active transport system, suggesting that OAT4 may be localized to the apical membrane in renal tubules.…”
Section: Oat4 (Slc22a11)mentioning
confidence: 83%
See 1 more Smart Citation
“…Trans-stimulation of OAT4 was not observed in earlier studies. Furthermore, unlike Oat1 and Oat3, OAT4's function was reported to be sodium-independent [72]. These findings contrasted with that of the renal basolateral tertiary active transport system, suggesting that OAT4 may be localized to the apical membrane in renal tubules.…”
Section: Oat4 (Slc22a11)mentioning
confidence: 83%
“…Its expression is evident in the kidney and placenta [72]. Studies addressing OAT4's mechanism of transport are inconclusive, and somewhat conflicting.…”
Section: Oat4 (Slc22a11)mentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30] OAT4 is an apical organic anion/dicarboxylate exchanger, which mainly functions under physiological conditions as an apical pathway for the reabsorption of some organic anions from urine into tubular cells, driven by an outwardly directed dicarboxylate gradient, probably with coupling to apical organic efflux transporters, such as MRP2, NPT1 and, possibly, the human homologue of OATv1. 25 NPT1 expressed in Xenopus laevis oocytes transports estradiol-17β-glucuronide, PAH, benzylpenicillin, faropenem, indomethacin and uric acid and an has affinity for several organic anions, including 2-ketoglutaric acid, β-lactam antibiotics (ampicillin, cefazolin, cephalexin), benzoic acid, lactic acid, probenecid and phenol red.…”
Section: ) Elimination From the Kidneymentioning
confidence: 99%
“…Cha et al found high levels of mRNA expression of OAT4 in the placenta and the kidney, whereas rOAT2 and hOAT3 are not expressed in the placenta 22 The expression of OAT1 in the placenta is extremely weak or absent, and OAT4 is predominantly expressed in the placenta among OAT isoforms. 22 Since OAT4 is a tertiary active organic anion/dicarboxylate exchanger under physiological conditions, it might be responsible for the elimination and detoxication of estrone sulfate and other organic anions, such as NSAIDs, diuretics, sulfobromophthalein, benzylpenicillin and bile acids, which interact with this transporter. 22 Two other excretory pathways have been identified in the placenta.…”
Section: -2) Blood-placenta Barriermentioning
confidence: 99%
See 1 more Smart Citation